Sponsor Reputation and Capital Structure Dynamics in Leveraged Buyouts - Shive, Sophie; Forster, Margaret (Management Science, 2025)
We examine whether leveraged buyout (LBO) sponsors’ reputations as borrowers affect the refinancing terms of their portfolio companies. In 510 U.S. LBOs for which we can reconstruct debt financing activity, 67% of financing events occur one quarter before the earliest existing debt maturity. These On Time events generally improve borrowing terms, whereas Early events feature more dividends, leverage, and higher cost. In each case, dividend issuance decreases and cost increases with the proportion of the sponsors’ recent exits that are failures. Effects are absent for matched firms and prior to the LBO and are procyclical; sponsors with recent failures miss opportunities to decrease financing costs in good times. This paper was accepted by Bo Becker, finance. Supplemental Material: The data files are available at https://doi.org/10.1287/mnsc.2023.00971 .